Trigeminal Cardiac Reflex: New Thinking Model About the Definition Based on a Literature Review. Issue 5 (February 2015) - Meuwly, C.; Golanov, E.; Chowdhury, T.; Erne, P.; Schaller, B.
Abstract : Abstract: Trigeminocardiac reflex (TCR) is a brainstem reflex that manifests as sudden onset of hemodynamic perturbation in blood pressure (MABP) and heart rate (HR), as apnea and as gastric hypermotility during stimulation of any branches of the trigeminal nerve. The molecular and clinical knowledge about the TCR is in a constant growth since 1999, what implies a current need of a review about its definition in this changing context. Relevant literature was identified through searching in PubMed (MEDLINE) and Google scholar database for the terms TCR, oculocardiac reflex, diving reflex, vasovagale response. The definition of the TCR varies in clinical as well as in research studies. The main difference applies the required change of MABP and sometimes also HR, which most varies between 10% and 20%. Due to this definition problem, we defined, related to actual literature, 2 major (plausibility, reversibility) and 2 minor criteria (repetition, prevention) for a more proper identification of the TCR in a clinical or research setting. Latest research implies that there is a need for a more extended classification with 2 additional subgroups, considering also the diving reflex and the brainstem reflex. In this review, we highlighted criteria for proper definition and classification of the TCR in the light of increased knowledge and present a thinking model to overcome this complexity. Further we separately discussed the role of HR and MABP and their variation in this context. As another subtopic we gave attention to is the chronic TCR; a variant that is rarely seen in clinical medicine.